Nigeria’s Volatile Oil Revenue: Is There a Cause for Concern? - Ogunjumo, Rotimi Ayoade; Musa, Nuhu; Adama, Ibrahim; Abu, Silas Idoko; Inedu, Hitlar; Hamzat, Salami; Ibitowa, Stephen Adesina (International Journal of Energy Economics and Policy, 2024)
This study, unlike previous studies, investigates the impact of volatile oil revenue on economic growth in Nigeria from 1986-2020. The study adopted the Auto-Regressive Distributed Lag technique (ARDL) to analyze the data. The results show that in the short-run, oil revenue volatility significantly depressed economic growth. In the long-run, however, oil revenue volatility improves economic growth in the country. The study therefore recommends that governments and policymakers in Nigeria should vigorously pursue policies that will reduce the reliance on oil revenue through greater economic diversification; otherwise economic growth may worsen in the short-run.